Roles Played by Stress-Induced Pathways in Driving Ethnic Heterogeneity for Inflammatory Skin Diseases - Jamerson, Taylor A.; Li, Qinmengge; Sreeskandarajan, Sutharzan; Budunova, Irina V.; He, Zhi; Kang, Jian; Gudjonsson, Johann E.; Patrick, Matthew T.; Tsoi, Lam C. (Frontiers in Immunology, 2022)
Immune-mediated skin conditions (IMSCs) are a diverse group of autoimmune diseases associated with significant disease burden. Atopic dermatitis and psoriasis are among the most common IMSCs in the United States and have disproportionate impact on racial and ethnic minorities. African American patients are more likely to develop atopic dermatitis compared to their European American counterparts; and despite lower prevalence of psoriasis among this group, African American patients can suffer from more extensive disease involvement, significant post-inflammatory changes, and a decreased quality of life. While recent studies have been focused on the understanding the heterogeneity in underlying disease mechanisms and genetic factors at play, little emphasis has been put on the effect of psychosocial or psychological stress on immune pathways, and how these factors contribute to differences in clinical severity, prevalence, and treatment response across ethnic groups. In this review, we explore the heterogeneity of atopic dermatitis and psoriasis between African American and European American patients by summarizing epidemiological studies, address potential molecular and environmental factors, with a focus on the intersection between stress and inflammatory pathways.